Factorial Study on the Effects of b-Cyclodextrin and Sodium Lauryl Sulphate on the Solubility and Dissolution Rate of Celecoxib Tablets - Chowdary, K.P.R.; Gopichand, G. (Asian Journal of Chemistry, 2010)
The objective of the study is to evaluate the individual and combined (or interaction) effects of b -cyclodextrin (bCD) and sodium lauryl sulphate (SLS), a surfactant on the solubility and2 factorial study. the solubility of celecoxib in the fourbCD and SLS, as per 22-factorial study, was determined. The solubilitybCD (3.27 fold), SLS (15.84 fold) individually as wellbCD and SLSp < 0.01). Celecoxib tablets were formulated employing selected combinationsbCD and SLS as per a 22 factorial design and were evaluated. The individual mainbCD, SLS and their combined effects in enhancing the dissolution rate of celecoxibp < 0.05). b-Cyclodextrin and SLS alone gave higher enhancement inbCD and SLS was used in the tablets. dissolution rate of celecoxib tablets in a 2 selected fluids containing of celecoxib was markedly enhanced by as in combined form (28.40 fold). Both the individual and combined effects of were highly significant ( of effects of tablets wer significant ( dissolution rate of celecoxib tablets (2.39-2.46 fold). There was no additional increase in the dissolution rate of celecoxib when a combination of